Serendipity in anthropological research [ the nomadic turn - Hazan, Haim; Hertzog, Esther (Ashgate, 2012)
Serendipity in Anthropological Research explores the role of fortune and happenstance in anthropology. It conceives of anthropological research as a lifelong nomadic journey of discovery in which the world yields an infinite number of unexplored issues and innumerable ways of studying them.